Radiotherapy Treatment for Melanoma Skin Cancer Disease - Tabitha Grace Larasati; Josephine Elsa Diani Putranto; Anggun Anggun; Frichilya Intan Lawa Padang; Wahyu Irawati (BIOEDUSCIENCE, 2021)
Background: Melanoma is a skin disorder caused by malignant degeneration of the pigment cells melanocytes. The disease is characterized by widespread discoloration with irregular and protruding edges. In treating cancer itself, radiotherapy technology, has been found. It is a method of treating cancer using high-energy radiation rays that are focused on cancerous tissue to kill or stop cancer cell division. This study aims to determine the effectiveness of radiotherapy technology as a treatment solution for melanoma skin cancer. The focuses of the study in this paper are the integumentary system and skin structure, melanoma skin cancer, the body's mechanisms for melanoma skin cancer, and radiotherapy as a treatment method. Methods: The research method used is literature study from various sources, to help understand the problem more deeply and completely. Conclusions: Melanoma, which attacks one of the body's integumentary systems, namely the skin, has a close relationship with homeostatic dysregulation and endocrine damage. However, radiotherapy method can be used to cure melanoma skin cancer by shooting X-rays and damaging the cancer cells and also reducing their spread to other parts of the organs. This method is effective because melanoma skin cancer is localized or has not spread to other organs. However, the use of radiotherapy can also have a negative impact on the body and can give unwanted side effects, so consideration is needed before using this method.